ANALYSIS OF WATER QUALITY AND BENEFIT VALUE OF HYDROLOGICAL CONTRIBUTION PROTECTED FOREST AREA IN THE CISANTI LAKE ( UPSTREAM CITARUM WATERSHED) BANDUNG REGENCY, JAWA BARAT - SETIYANI (Nim : 11514044), AGIS
The protected forest area around Cisanti Lake in DAS Citarum River has a function as a provider ecosystem in the form of water. The ability of forest to provide the useful of hydrological until now it is considered not able to enter the market system because it is intangible. It is due to the public appreciation of the water resource produced is still low. Hence, the information about economic value of protected forest area in the Cisanti Lake and the water quality is really important to be known to protect the water resource in protected forest area. The aims of this research are: (1) to determine the quality of the water in the Cisanti lake in the year of 2014-2018; (2) to determine the quality status of water springs in Cisadane, Cisanti lake and river flow originating from Cisanti lake; (3) to identify the socialeconomy which influence the water consumption in the household sector; (4) to determine the economic value of the useful of water in protected forest area in Cisanti lake in the household and agricultural sector. Determination of the status of air quality is done using the storet method. Identification of socioeconomic variables obtained through interviews and questionnaires followed by multiple regression analysis using stepwise forward and F test methods using SPSS 22. Determination of sample size of respondents using the Slovin formula with stratified random sampling technique. The method of the costing method is used to determine the value of water benefits from the household sector while the value of the benefits of water in the agricultural sector uses the method of market value (productivity) approach. The results showed that the water quality at the Situ Cisanti outlet within the last five years did not meet the class 1 water quality standard. The water quality status in the Cisadane spring meets the class 1 water quality standard, Situ Cisanti does not meet the class 1 water quality standard, while the river water meets the class 1 water quality standard. Socioeconomic variables that affect the household water consumption include the amount of water procurement costs (X1), income (X2), and the water scarcity intensity (X8) with the regression model equation Y = 386,691-0,00019X1+1,6824X2 -19,209 X8 and R2 value of 50,2%. The value of water benefits in the household sector and the agricultural sector are Rp. 187,248,575,940 per year and Rp. 317,011,044,240 per year. Based on the value of the water benefits, the estimated value of the conservation fund for Situ Cisanti conservation is Rp 504.259.620.180 per year.